Haemato-Biochemical Studies on Theileria Equi Infection in Seropositive Horses - Bhojani, Rakesh J.; Chahar, Anju; Dedar, Ramesh Kumar; Kachhawa, Jai Prakash (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
This study aimed to know the haemato-biochemical changes associated with Theileria equi (T. equi) infection in five horse-populatedareas/district of Rajasthan viz., Bikaner, Ajmer, Barmer, Nagaur, and Pali. Total 151 horses, irrespective of age and sex, were screened forT.equi infection. Whole blood and sera samples of all these horses were studied for haematology (Hb, PCV, total RBC, and WBC count),serum biochemistry (SGOT, ALP, GGT, and total bilirubin), and serological test like c-ELISA. On the basis of c-ELISA test, the overallseroprevalence of T. equi was 49.66%. Haemato-biochemical studies in seropositive horses revealed none significantly low value ofhaemoglobin, packed cell volume, total erythrocyte count, and none significantly higher GGT, ALP, and total bilirubin when comparedwith apparently healthy seronegative horses. Haemato-biochemical studies in seropositive horses revealed a significantly lower valueof total leucocyte count and a significantly higher value of SGOT than apparently healthy seronegative horses.
Keywords: c-ELISA; Haemato-biochemistry; Horses; Rajasthan; Theileria equi